Peningkatan Kapasitas Tenaga Penyelenggara Makanan Darurat Bencana melalui Penyuluhan di Desa Sukarasa, Salawu, Tasikmalaya - Sumarto Sumarto; Ani Radiati; Yanita Listianasari (Institut Pertanian Bogor, 2019)
Tasikmalaya District is the second most disaster-prone area in Indonesia. Landslides and earthquakes were last disaster that occurred in Sukarasa Village, Salawu Sub-district, Tasikmalaya. Food management during disasters in the area was carried out with various obstacles, so preparedness efforts are needed in the implementation of effective and efficient food management. The purpose of this activity was to strengthening the capacity of the Regional Disaster Management Agency (RDMA) and communities in disaster-prone areas in preparing food for the needs of disaster victims through a education. This activity was carried out during July-October 2018. The main method of this activity were the preparation of technical guidelines for implementetion of disaster emergency food with RDMA Tasikmalaya and education to the target groups.This activity has produced a technical guideline book with the title in disaster emergency conditions with the utilization of local resources. The book has been declared feasible to be issued by the RDMA of Tasikmalaya District and obtained Copyright Number EC00201851988 and ISBN Number 978-602-51817-9-5. The application of the book in the form of extension and practice to the residents of Sukarasa Village, Salawu Sub-district volunteers, and BPBD staff in Tasikmalaya District showed an increase in knowledge and skills in preparing recipes and making ready-to-eat food products in disaster emergency conditions in accordance with the guidelines book.